Beta-carotene reduces body adiposity of mice via BCMO1. - Jaume Amengual; Erwan Gouranton; Yvonne G J van Helden; Susanne Hessel; Joan Ribot; Evelien Kramer; Beata Kiec-Wilk; Ursula Razny; Georg Lietz; Adrian Wyss; Aldona Dembinska-Kiec; Andreu Palou; et al. (PLoS ONE, 2011)
Evidence from cell culture studies indicates that β-carotene-(BC)-derived apocarotenoid signaling molecules can modulate the activities of nuclear receptors that regulate many aspects of adipocyte physiology. Two BC metabolizing enzymes, the BC-15,15'-oxygenase (Bcmo1) and the BC-9',10'-oxygenase (Bcdo2) are expressed in adipocytes. Bcmo1 catalyzes the conversion of BC into retinaldehyde and Bcdo2 into β-10'-apocarotenal and β-ionone. Here we analyzed the impact of BC on body adiposity of mice. To genetically dissect the roles of Bcmo1 and Bcdo2 in this process, we used wild-type and Bcmo1(-/-) mice for this study. In wild-type mice, BC was converted into retinoids. In contrast, Bcmo1(-/-) mice showed increased expression of Bcdo2 in adipocytes and β-10'-apocarotenol accumulated as the major BC derivative. In wild-type mice, BC significantly reduced body adiposity (by 28%), leptinemia and adipocyte size. Genome wide microarray analysis of inguinal white adipose tissue revealed a generalized decrease of mRNA expression of peroxisome proliferator-activated receptor γ (PPARγ) target genes. Consistently, the expression of this key transcription factor for lipogenesis was significantly reduced both on the mRNA and protein levels. Despite β-10'-apocarotenoid production, this effect of BC was absent in Bcmo1(-/-) mice, demonstrating that it was dependent on the Bcmo1-mediated production of retinoids. Our study evidences an important role of BC for the control of body adiposity in mice and identifies Bcmo1 as critical molecular player for the regulation of PPARγ activity in adipocytes.